The Effect of gamification, design and service on marketing strategy of Mobile Legend (ML) in Manado - Rangga Saputra Karundeng; Stanss L.H.V.J Lapian; Fitty Valdi Arie (Universitas Sam Ratulangi, 2022)
This study aims to determine the effect of gamification on the marketing strategy of Mobile Legend (ML) in Manado, the effect of design on the marketing strategy of Mobile Legend (ML) in Manado, the effect of service on the marketing strategies of Mobile Legend (ML) in Manado and the effect of gamification, design and service simultaneously on the marketing strategy of Mobile Legend (ML) in Manado. The research approach used in this research is quantitative using associative method. Collecting data in this study using research questionnaires. The data analysis technique in this study used multiple linear regression analysis. The results showed that (1) Gamification had a significant effect on the Marketing Strategy of Mobile Legend (ML) in Manado, (2) Design had a significant effect on the Marketing Strategy of Mobile Legend (ML) in Manado, (3) Service had a significant effect on the Marketing Strategy of Mobile Legend (ML) in Manado and (4) Gamification, Design and Services have a significant effect on the Marketing Strategy of Mobile Legend (ML) in Manado